The Principles Of Land Lease Agreement And The Formulation Of Profit Sharing In The Framework Of Building Right Titles And The Rigt To Use Titles - Hasmonel Hasmonel; Lego Karjoko (University of Sang Bumi Ruwa Jurai, 2017)
This research is a formulation model of profit sharing principle in land lease agreement in the framework of giving Building Rights Titles / Right to Use Titles which aims to resolve land conflicts as a result of the imbalance of agrarian structure in Indonesia and to balance the rights and obligations in land lease the provision of Building Right Titles (HGB), as well as formulating the principle of profit sharing principle in the land lease agreement in the framework of awarding Building Right Titles (HGB) / Right to Use Titles above Freehold Titles. This research used qualitative research method with symbolic interaction as research strategy, that is, reconstruct adjustment of action from three subject of legal relation that is holder of HGB / Freehold Titles, holder of Freehold Titles (HM) and National Land Agency.The conclusion of this research suggests that the HM holder agreement with the HGB winner as a tenant is required to interfere with government policy, which is to harmonize and protect the interests of holders of Freehold Titles and tenants in the form of profit sharing principles in the provision of HGB / Right to Use Titles on Freehold Titles. begins with a land lease agreement, with the profit sharing principle having to consider the dominant factors affecting the amount of land rent that is just and sustainable, such as the location of the land, the selling value of the tax object, the market price of the land, the operational cost, and the existing building.